DEVELOPING ENGLISH SPEAKING MATERIALS OF DESCRIPTIVE TEXT BASED ON SCIENTIFIC APPROACH FOR STUDENTS OF MARKETING STUDY PROGRAM AT SMK NEGERI 1 MEDAN - Suhaila Muliani Lubis; Rahmad Husein (Universitas Negeri Medan, 2024)
The objective of this research was to develop English speaking materials of descriptive text for Tenth Grade students of Marketing Study Program at SMK based on scientific approach. The subjects of the research were grade X students of marketing study program at SMK Negeri 1 Medan. This research was classified as Research and Development (R&D). The research procedure was adapted from the research procedure proposed by Gall, Gall and Borg (2003). There were two questionnaires used to collect the data. The first questionnaire was used to collect data in need analysis while the second questionnaire was used to collect the data about the appropriateness of the materials in the expert judgment. The data was analyzed using descriptive statistics. The research findings showed that English speaking materials of descriptive text developed have met good characteristic and appropriate for grade ten students of marketing study program. It was indicated by the mean of expert judgments. The mean score for content is 3.5 which categorized as “Very Good”. The mean score for language is 3.8 which categorized as “Very Good”. The mean score for presentation is 3.5 which categorized as “Very Good”. The mean score for graphic is 3.75 which categorized as “Very Good”.